1997
DOI: 10.1074/jbc.272.7.3871
|View full text |Cite
|
Sign up to set email alerts
|

RGS Proteins and Signaling by Heterotrimeric G Proteins

Abstract: A ubiquitously employed mechanism for signal transduction involves ligand binding to a cell surface receptor coupled to a heterotrimeric guanine nucleotide-binding protein (G protein). Receptor activation stimulates nucleotide exchange and dissociation of the G protein, releasing the G␣ subunit in its GTP-bound state from the G␤␥ complex. The released subunits can stimulate a variety of target (effector) enzymes (1), thereby eliciting biochemical responses and changes in cellular physiology. Hundreds of G prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
370
1
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(381 citation statements)
references
References 60 publications
7
370
1
3
Order By: Relevance
“…Recently, novel regulatory molecules for these G-protein signaling pathways, termed RGS, have been identified (Koelle and Horvits 1996;Koelle 1997;Dohlman and Thorner 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel regulatory molecules for these G-protein signaling pathways, termed RGS, have been identified (Koelle and Horvits 1996;Koelle 1997;Dohlman and Thorner 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A recently appreciated form of regulation has come from the discovery that members of a protein family called regulators of G protein signaling, or RGS proteins, stimulate the rate of GTP hydrolysis by G protein ␣ subunits (3)(4)(5). RGS proteins are found in species ranging from yeast to mammals and constitute a family of at least 20 mammalian proteins (6)(7)(8).…”
mentioning
confidence: 99%
“…This is not surprising as many RGS proteins function against more than one Gα subunit and, in a reciprocal arrangement, several mammalian RGS proteins have been shown to act as GAPs for GPA1 in the Sc. cerevisiae pheromone-response pathway [6]. However, this is the first demonstration that the Sz.…”
Section: Shmoo Formation -In Addition To the Transcription Of Pheromomentioning
confidence: 88%
“…Most studies use the pheromoneresponse pathway within the budding yeast Saccharomyces cerevisiae and have made a number of significant contributions to our understanding of GPCR signalling [5][6][7]. Although many components can be functionally replaced by their mammalian counterparts [8], few studies have reported the expression of non-yeast Gα proteins in Sc.…”
Section: Introductionmentioning
confidence: 99%